Psychological Capital, Social Support and Wellbeing in Mothers of Children With Autism Spectrum Disorder - Sarwar Farhan; Panatik Siti Aisyah; Jameel Hafiz Tahir; Yunus Wan Mohd Azam Wan Mohd; Muhamad Siti Norlina (SAGE PUBLICATIONS INC, 2022)
This study examined the association between perceived social support, parental psychological capital, and multiple dimensions of mental well-being in mothers of children with autism. Psychological capital was assessed as a mediator in the proposed model. Data were collected from 112 mothers recruited from autism institutes in two cities of Pakistan. Analysis was done using partial least square structural equation modeling. The findings revealed that social support and psychological capital had a significant direct relationship with life satisfaction and perceived stress. Only psychological capital was related to parental satisfaction and negative affect. We found that psychological capital mediated the path between social support and all four dimensions of well-being outcomes. Our study shows that the informal social support enhances the multiple dimension of well-being of mothers of autistic children by enhancing their personality resource of psychological capital.